2008
DOI: 10.1080/17451590809618183
|View full text |Cite
|
Sign up to set email alerts
|

Floristics and structure of southwestern Bangladesh homegardens

Abstract: SUMMARYHomegardening is a traditional agroforestry practice in Bangladesh. Diverse species composition in a complex structure is a characteristic feature of Bangladesh homegardens. This study investigated the floristic and structural characteristics of homegardens from 402 randomly selected households in southwestern Bangladesh. A total of 419 species in 109 families were recorded. Fifty-nine per cent of all species were native to the Indian Subcontinent, including six IUCN Red-Listed for Bangladesh. Seventy-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Homesteads are privately owned dwelling areas in rural and semi-urban settings that include a dwelling unit equipped with a kitchen, backyard, front yard and occasionally a pond and home garden. A homestead forest or home garden is a mixture of deliberately planted vegetation, usually with a complex structure and designed to produce natural products for household consumption or for the market (Vogl and Vogl-Lukasser 2003;Kabir and Webb 2008a, 2008b, 2009. Homestead forest comprises 2% (2951.40 km 2 ) of the total land area of Bangladesh, which spreads over 20 million homesteads (Salam et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homesteads are privately owned dwelling areas in rural and semi-urban settings that include a dwelling unit equipped with a kitchen, backyard, front yard and occasionally a pond and home garden. A homestead forest or home garden is a mixture of deliberately planted vegetation, usually with a complex structure and designed to produce natural products for household consumption or for the market (Vogl and Vogl-Lukasser 2003;Kabir and Webb 2008a, 2008b, 2009. Homestead forest comprises 2% (2951.40 km 2 ) of the total land area of Bangladesh, which spreads over 20 million homesteads (Salam et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many studies have been carried out on this concept and examined the different aspects on homestead forestry. Notable past studies pertaining to our current research include the National Forest andTree Resources Assessment 2005-2007 Bangladesh (GOB 2009a), structure, floristics, vegetation characteristics and indigenous management of Bangladesh home garden (Mustafa et al 1996(Mustafa et al , 2000Mustafa and Haruni 2002); flood plain tree resources (Miah and Hossain 2002); home-garden-farming system (Ali 2005); structure and diversity of home garden agro-forestry (Zaman et al 2010); farmer's perceptions on planting trees in homesteads (Salam et al 2000); homestead biodiversity, floristics and characteristics (Kabir and Webb 2008a, 2008b, 2009; along with the previous works of Douglas (1981), Hammermaster (1981) and others. Past studies confirmed that homestead forests are rich in diversified plants and contribute considerable role in the rural livelihood of Bangladesh, especially in terms of providing firewood and timber.…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, various studies, for example, [3,7,9,[16][17][18][19][20][21][22][23] explore the floristic composition (mainly trees) in the homestead gardens; homestead agroforestry system by [24][25][26]; homestead plantation and traditional uses by [27,28]; quantitative structure and silvicultural management by [29][30][31]; production and services by [32,33]. Moreover, Motiur et al [34] studied the role of homestead gardens in rural economy; Alam and Masum [35] and Masum et al [8] studied the status of homestead garden in an offshore island of Bangladesh, and Akhter et al [36] studied the role of women in homestead gardens management in the northeastern Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies on Home gardens have been done by different workers in the world (Soemarwofo 1987;Abdoellah 1990;Perera & Rajapakse 1991;Michon & Mary 1994;Agelet et al 2000;Leiva et al 2001;Kabir & Webb 2008;Talemos et al 2014). Several workers studied Home garden system in India.…”
Section: Introductionmentioning
confidence: 99%